1996
DOI: 10.1183/09031936.96.09102087
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between asthma admission rates, routes of admission, and socioeconomic deprivation

Abstract: T Th he e r re el la at ti io on ns sh hi ip p b be et tw we ee en n a as st th hm ma a a ad dm mi is ss si io on n r ra at te es s, , r ro ou ut te es s o of f a ad dm mi is ss si io on n, , a an nd d s so oc ci io oe ec co on no om mi ic c d de ep pr ri iv va at ti io on n ABSTRACT: This study aimed to explore the relationship between hospital admissions for asthma and socioeconomic deprivation. A retrospective study examined one year of hospital admissions for asthma in the West Midlands region of England (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
4
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 47 publications
(56 reference statements)
1
60
4
1
Order By: Relevance
“…In contrast to the suggestions from ecological studies, [10][11][12] but in line with other individual-level studies, [14][15][16][17][18] material deprivation was not observed to be an important independent risk factor for admission.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to the suggestions from ecological studies, [10][11][12] but in line with other individual-level studies, [14][15][16][17][18] material deprivation was not observed to be an important independent risk factor for admission.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
“…Several ecological studies suggest that socioeconomic status may be an important determinant of respiratory admissions, [10][11][12] but evidence at individual level is limited and conflicting. [13][14][15][16][17][18][19] A large cohort study of 14 223 adults in Copenhagen found that education and income were significant predictors of COPD admission, but unfortunately this study did not assess the impact of all important confounders.…”
Section: Introductionmentioning
confidence: 99%
“…10,28,[37][38][39][40] There is no explanation for the finding. According to Rona,18 poverty is not a risk factor for the appearance of asthma, but an aggravating factor.…”
Section: Discussionmentioning
confidence: 47%
“…Alternatively, re-hospitalization may act as a poor marker of severity of illness; non-biological factors such as holidays, insurance status, socioeconomic status, and provider-patient interactions may influence the decision to hospitalize a child. (27)(28)(29)(30)(31)(32)(33)(34) Similarly, there was no significant difference in parental report of "wheezing or whistling in the chest." Although a true lack of drug effect is possible, another explanation is that parents did not accurately identify wheezing.…”
Section: Discussionmentioning
confidence: 87%